Performance Of Physical Education Teachers In The New Normal Of Covid-19 - Damrah Damrah; Suci Novita; Yuni Astuti; Pitnawati Pitnawati; Erianti Erianti; Zulbahri Zulbahri (UNIB Press, 2021)
Based on the safety of the SMPN in North Padang in this new normal time, it is seen that the physical education teacher's performance of sports and health is still low. This research aims to find out how physical education teachers 'performance of sports and health is seen from the new normal learning planning, the implementation of new normal learning and a normal new time learning evaluation. This type of research is combined research (Mixed Method), the first step in the study with quantitative methods, while the second step is using qualitative. In this study, the research study was conducted using the total sampling technique. Techniques of data collection process using interviews, polls, and documentation. Data analysis techniques used in triangulation. The results of this research show, judging by the normal new time Learning Plan (28.57%) Category is not good. For a fairly valued category (28.57%). For a good category of worth (28.57%), for the category is very well worth (0.00%). Implementation of the new Normal learning (0.00%) Category is not good. For a fairly valued category (42.86%). For good category worth (42.86%), for very good category worth (0.00%) Evaluation/assessment of the new normal study (28.57%) Category is not good. For a fairly valued category (42.85%). For good category worth (14.29%), for the category is very well worth (0.00%). As for the qualitative results of interviews conducted with the physical education teachers at the SMPN of North Padang City, it is stated that the learning planning of physical education and sports teachers is good enough for the implementation of learning in the new normal can be categorized as a lack of good, for the evaluation/assessment of learning in the new normal future.